EFFICACY OF PRESYNCH-OVSYNCH-56 PROTOCOL IN INCREASING THE CONCEPTION RATE IN REPEAT BREEDER COWS - HEMALATHA, H; KANTHARAJ, S; MURUGAVEL, K; RAJU, M S; ANTOINE, D (The Indian Journal of Animal Reproduction, 2022)
A total of 30 repeat breeder cows that did not conceive even after three or more inseminations were divided intotwo equal groups. Cows in Group-I were kept as control and inseminated once during the observed estrus. Cows inGroup-II (Treatment) were subjected to Presynch-Ovsynch-56 protocol and subjected to Fixed Time ArtificialInsemination. Blood was collected from both the groups on the day of AI and day 6 post-AI for serum progesteroneestimation. Cows in both groups that returned to estrus following the first AI were re-inseminated. There was nosignificant difference in the mean serum progesterone concentration between the groups both on the day of AI andday 6 post-AI. There was no significant difference in the first, second service and overall conception rate between thegroups. However, Presynch-Ovsynch-56 protocol resulted in an acceptable overall conception rate of 33.33 % inrepeat breeder cows compared to 20 % obtained in control repeat breeder cows.
Keywords: Presynch-Ovsynch-56; Repeat breeder cows; Conception rate